Hoax di Media Sosial Facebook: Antara Edukasi dan Propaganda Kepentingan - Muhamad Tisna Nugraha (JSW (Jurnal Sosiologi Walisongo), 2019)
Technological advances have encouraged the raise of a variety of social media services features which are more and more innovative, interesting, and variative. This technological development impacting in human civilization, especially pertaining to multidimensional as well as multilateral interaction. The benefit of social media was accompanied by the negative side, such as slander, conflict, nation- disintegration, and separatism. This is a qualitative research applying case- study approach. The instruments used in this research are documentation, observation, and library research. The conclusion is that education has an important role in using social media. Otherwise, social media will only be used as the media for committing crime, including disseminating tendentious words, hoax, and propaganda